Stabilization of Azapeptides by N-amide center dot center dot center dot H-N-amide Hydrogen Bonds - Baruah, Kalpita; Sahariah, Biswajit; Sakpal, Sushil S.; Deka, Jugal Kishore Rai; Bar, Arun Kumar; Bagchi, Sayan; Sarma, Bani Kanta (Organic Letters, 2021)
An unusual N-amide center dot center dot center dot H-Namide hydrogen bond (HB) was previously proposed to stabilize the azapeptide beta-turns. Herein we provide experimental evidence for the N-amide center dot center dot center dot H-Namide HB and show that this HB endows a stabilization of 1-3 kcal.mol(-1) and enforces the trans-cis-trans (t-c-t) and cis-cis-trans (c-c-t) amide bond conformations in azapeptides and N-methyl-azapeptides, respectively. Our results indicate that these N-amide center dot center dot center dot H-Namide HBs can have stabilizing contributions even in short azapeptides that cannot fold to form beta-turns.